Eminent Antimicrobial Peptide Resistance in Zymomonas mobilis: A Novel Advantage of Intrinsically Uncoupled Energetics - Reinis Rutkis; Zane Lasa; Marta Rubina; Inese Strazdina; Uldis Kalnenieks (MDPI AG, 2024)
Relative to several model bacteria, the ethanologenic bacterium Zymomonas mobilis is shown here to have elevated resistance to exogenous antimicrobial peptides (AMPs)- with regard to both peptide bulk concentration in the medium and the numbers of peptide molecules per cell. By monitoring the integration of AMPs in the bacterial cell membrane and observing the resulting effect on membrane energy coupling, it is concluded that the membranotropic effects of the tested AMPs in Z. mobilis and in Escherichia coli are comparable. The advantage of Z. mobilis over E. coli apparently results from its uncoupled mode of energy metabolism that, in contrast to E. coli, does not rely on oxidative phosphorylation, and hence, is less vulnerable to the disruption of its energy-coupling membrane by AMPs. It is concluded that the high resistance to antimicrobial peptides (AMPs) observed in Z. mobilis not only proves crucial for its survival in its natural environment but also offers a promising platform for AMP production and sheds light on potential strategies for novel resistance development in clinical settings.